Differences in end‐of‐life communication for children with advanced cancer who were referred to a palliative care team. Issue 8 (16th April 2015) - Kassam, Alisha; Skiadaresis, Julia; Alexander, Sarah; Wolfe, Joanne
Abstract : Background: There is a general consensus that involving a specialized palliative care team in the care of children with advanced cancer can help optimize end‐of‐life communication; however, how this compares to standard oncology care is still unknown. We aimed to determine whether there was an association between specialist palliative care involvement and improved end‐of‐life communication for children with advanced cancer and their families. Procedure: We administered questionnaires to 75 bereaved parents (response rate 54%). Outcome measures were presence or absence of 11 elements related to end‐of‐life communication. Results: Parents were significantly more likely to receive five communication elements if their child was referred to a palliative care team. These elements are: discussion of death and dying with parents by the healthcare team ( P  < 0.01); discussion of death and dying with child by the healthcare team when appropriate ( P  < 0.01); providing parents with guidance on how to talk to their child about death and dying when appropriate ( P  < 0.01); preparing parents for medical aspects surrounding death ( P  = 0.02) and sibling support ( P  = 0.02). Children were less likely to be referred to a palliative care team if they had a hematologic malignancy. Conclusions: Children who receive standard oncology care are at higher risk of not receiving critical communication elements at end of life. Strategies to optimize end‐of‐life communication for children who are not referred to a palliative care team are needed. Pediatr Blood Cancer 2015;62:1409–1413. © 2015 Wiley Periodicals, Inc.